2015
DOI: 10.1007/s12011-015-0423-3
|View full text |Cite
|
Sign up to set email alerts
|

Intracellular Zn2+ Increase in Cardiomyocytes Induces both Electrical and Mechanical Dysfunction in Heart via Endogenous Generation of Reactive Nitrogen Species

Abstract: Oxidants increase intracellular free Zn(2+) concentration ([Zn(2+)]i) in ventricular myocytes, which contributes to oxidant-induced alterations in excitation-contraction coupling (ECC). However, it is not clear whether increased [Zn(2+)]i in cardiomyocytes via increased reactive nitrogen species (RNS) has a role on heart function under pathological conditions, such as hyperglycemia. In this study, first we aimed to investigate the role of increased [Zn(2+)]i under in vitro condition in the development of both … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
25
0
1

Year Published

2017
2017
2024
2024

Publication Types

Select...
4
2

Relationship

2
4

Authors

Journals

citations
Cited by 34 publications
(26 citation statements)
references
References 41 publications
0
25
0
1
Order By: Relevance
“…Most importantly, it has been clearly documented that ROS and RNS can cause a marked increase in cytosolic and mitochondrial Zn 2+ release under pathological condition in the heart (Lin et al, ) via a role with increased [Zn 2+ ] i as a second messenger of extracellular signals similar to [Ca 2+ ] i (Tuncay et al, ). Consequently, increased [Zn 2+ ] i could induce marked depression in the contractile activity of the heart (Tuncay & Turan, ). In this regard, the present findings clearly express the important mediator roles of β 3 ‐AR activation in ventricular cardiomyocytes together with the increased expression level of β 3 ‐AR in ventricular cardiomyocytes from MetS rats, in part, via a relation between elevated [Zn 2+ ] i and increased RNS.…”
Section: Discussionmentioning
confidence: 99%
“…Most importantly, it has been clearly documented that ROS and RNS can cause a marked increase in cytosolic and mitochondrial Zn 2+ release under pathological condition in the heart (Lin et al, ) via a role with increased [Zn 2+ ] i as a second messenger of extracellular signals similar to [Ca 2+ ] i (Tuncay et al, ). Consequently, increased [Zn 2+ ] i could induce marked depression in the contractile activity of the heart (Tuncay & Turan, ). In this regard, the present findings clearly express the important mediator roles of β 3 ‐AR activation in ventricular cardiomyocytes together with the increased expression level of β 3 ‐AR in ventricular cardiomyocytes from MetS rats, in part, via a relation between elevated [Zn 2+ ] i and increased RNS.…”
Section: Discussionmentioning
confidence: 99%
“…It is now well accepted that a well-controlled Zn 2+ homeostasis via Zn 2+ regulatory mechanisms can control influx/efflux of zinc to prevent toxic zinc accumulation into cells, particularly endogenous labile Zn 2+ plays a significant role in cytotoxic events at single cell level, including cardiomyocytes [ 8 , 9 , 10 , 40 , 51 ]. As mentioned in many articles, Zn 2+ is essential for growth and development for both plants and mammalians.…”
Section: Role Of Zinc In Human Healthmentioning
confidence: 99%
“…Thus, the area of Zn 2+ -homeostasis seems to be emerging in cardiovascular disease. However, it has been demonstrated that labile Zn 2+ outside a narrow concentration range are toxic to a variety of cells [ 69 ], including cardiomyocytes [ 8 , 9 , 10 , 14 , 40 , 51 , 75 ].…”
Section: Labile Zn 2+ In Cardiac Physiology Andmentioning
confidence: 99%
See 2 more Smart Citations